Novel digital continuous sensor for monitoring of compartment pressure: a case report. Issue 3 (29th September 2022) - Montreuil, Julien; Corban, Jason; Reindl, Rudolf; Harvey, Edward J.; Bernstein, Mitchell
Abstract: Case: The American Academy of Orthopaedic Surgeons has recently identified continuous intracompartmental pressure monitoring as 1 of the few means to assist in ruling out acute compartment syndrome (ACS). There are very few methods that allow this measurement. This manuscript describes the use of a new digital monitoring system for ACS in 3 patients. This minimally invasive device, the MY01 (NXTSENS, Montreal, Canada) is capable of continuously and precisely measuring variations in intracompartmental pressure. Conclusion: MY01 detected the occurrence of ACS at early-stage and expedited the timing of surgery for 2 patients. This tool also objectively excluded a suspected diagnosis of ACS in a medically comorbid patient, obviating the need for unnecessary fasciotomies and potential complications.